2010
DOI: 10.1097/ta.0b013e3181e5d35e
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Progenitor Cell Mobilization Is Mediated Through β-2 and β-3 Receptors After Injury

Abstract: Background Hematopoietic progenitor cells (HPCs) are mobilized into the peripheral blood (PB) and then sequestered in injured tissue after trauma. Nonselective β-adrenergic blockade (BB) has been shown to cause a decrease in mobilization of HPCs to the periphery and to injured tissue. Given the vast physiologic effects of nonselective BB, the aim of this study is to delineate the role of selective BB in HPC growth and mobilization. Methods Rats underwent daily intraperitoneal injections of propranolol (Prop)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 30 publications
5
58
0
Order By: Relevance
“…Neural and endocrine dynamics could also conceivably expand the total body pool of monocytes via increased hematopoietic output of myeloid lineage immune cells (myelopoiesis) (23). Hematopoiesis and monocyte differentiation occur in a bone marrow microenvironment that receives direct innervation from the sympathetic nervous system (SNS) (24), and SNS activation can alter hematopoietic stem cell mobilization (25)(26)(27) and myelopoietic responses to systemic infection (28,29). It is not known whether social processes can influence monocyte differentiation, or what role the SNS might play in such dynamics.…”
mentioning
confidence: 99%
“…Neural and endocrine dynamics could also conceivably expand the total body pool of monocytes via increased hematopoietic output of myeloid lineage immune cells (myelopoiesis) (23). Hematopoiesis and monocyte differentiation occur in a bone marrow microenvironment that receives direct innervation from the sympathetic nervous system (SNS) (24), and SNS activation can alter hematopoietic stem cell mobilization (25)(26)(27) and myelopoietic responses to systemic infection (28,29). It is not known whether social processes can influence monocyte differentiation, or what role the SNS might play in such dynamics.…”
mentioning
confidence: 99%
“…In a subsequent study, a team from the same laboratory [20] found that the protection is mediated by beta-2 and beta-3 receptors; the beta-1 receptor had no impact on BM HPC growth [20]. In this study, using an HS model, we demonstrated similarly that the BM is protected via non-selective BB administration either before or immediately after HS.…”
Section: Discussionmentioning
confidence: 51%
“…In a lung contusion model, A2 and A3 inhibition, as opposed to A1 inhibition, reduced both bone marrow suppression and hematopoietic precursor cell sequestration. 35 In a laparotomy model, cerebral immunologic changes were under BAR control, and not >-adrenergic receptor control, and BAR inhibition reduced proinflammatory cytokines. 36 BAR inhibition has also been studied in TBI models that we previously demonstrated with PET imaging and immunohistochemistry increased perfusion and reduced hypoxia with nonselective BAR inhibition.…”
Section: Discussionmentioning
confidence: 99%